2009
DOI: 10.21608/asat.2009.23704
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed DC Motor Sliding Mode Position Controller Design using Fuzzy Logic and PID Techniques

Abstract: Due to the robustness of sliding mode controllers (SMCs), especially against model uncertainties and disturbances, and also its ability in controlling nonlinear and multi-input multi-output (MIMO) systems; a DC motor sliding mode position controller design using fuzzy logic (FL) and proportional-integral-derivative (PID) techniques, is proposed in this paper. Also, due to system uncertainties that can lead to chattering phenomena in control law which can excite non-modeled dynamics and may damage the process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The Lypunove Stability Proof: Given that (17) Let us assume that the energy associated with the system is given as V(e). For the system to remain stable, then derivative of the energy associated with the system must be less than zero (or negative).…”
Section: Sliding Mode Controller Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The Lypunove Stability Proof: Given that (17) Let us assume that the energy associated with the system is given as V(e). For the system to remain stable, then derivative of the energy associated with the system must be less than zero (or negative).…”
Section: Sliding Mode Controller Designmentioning
confidence: 99%
“…The chattering problem associated with Bang-Bang control is eliminated by integrating the output of the discontinuous controller and also selecting suitable hysteresis boundary layer [16], [17]. The mathematical representation of the sliding mode discontinuous control is represented:…”
Section: Sliding Mode Controller Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The designed scheme contained the integrator to eliminate the steady state error and proved to be good for position tracking application. In [22], sliding mode was combined with PID and fuzzy logic technique to overcome chattering issue and applied this scheme on [23] enhanced the sliding mode with fuzzy logic control to overcome chattering issue and then controller was applied on position control of induction motor. It is shown that the designed controller behaved well in chattering reduction, and fast dynamic response is also achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In [14] the output of a PID controller is used as to establish the sliding surface of a Fuzzy SMC as applied in position control of a DC motor. Thus the controller structure incorporates a parallel control action by PID and Fuzzy logic Sliding mode (PID+FSMC).…”
Section: Introductionmentioning
confidence: 99%